From Receptor Selectivity to Functional Selectivity: The Rise of Biased Agonism in 5-HT1A Receptor Drug Discovery - Sniecikowska, Joanna; Newman-Tancredi, Adrian; Kolaczkowski, Marcin (Current Topics in Medicinal Chemistry, 2019)
Despite extensive efforts to design serotonin 5-HT1A receptor compounds, there are currently no clinically available selective agonists to explore the therapeutic potential of activating this receptor. Commonly used drugs targeting 5-HT1A receptors, such as buspirone or other azapirone compounds, possess only limited selectivity over cross-reacting sites, act as partial agonists for 5-HT1A receptor activation, and are metabolically labile, generating active metabolites. In addition, drug discovery has been hampered by the multiplicity of 5-HT1A receptor subpopulations, expressed in different brain regions, that are coupled to distinct molecular signaling mechanisms and mediate a wide variety of physiological responses, both desired and undesired. In this context, advances in 5-HT1A receptor drug discovery have attracted attention of novel ‘biased agonists’ that are selective, efficacious and preferentially target the brain regions that mediate therapeutic activity without triggering side effects. The prototypical first-in-class compound NLX-101 (a.k.a. F15599; 3-chloro-4-fluorophenyl-[4-fluoro-4-[[(5-methylpyrimidin-2-ylmethyl)amino]methyl]piperidin- 1-yl]methanone), preferentially activates 5-HT1A receptors in cortical regions and exhibits potent, rapidacting and sustained antidepressant-like and procognitive properties in animal models. Here the background has been reviewed that led to the discovery of the class of 1-(1-benzoylpiperidin-4- yl)methanamine derivatives, including NLX-101, as well as recent advances in discovery of novel 5-HT1A receptor biased agonists, notably aryloxyethyl derivatives of 1128;‘(1-benzoylpiperidin-4yl)methanamine which show promising pharmacological activity both in vitro and in vivo. Overall, the results suggest that opportunities exist for innovative drug discovery of selective 5-HT1A receptor biased agonists that may open new avenues for the treatment of CNS disorders involving dysfunction of serotonergic neurotransmission.
Keywords: Serotonergic neurotransmission